Modification of Learning Media Using Rubber Balls for Volleyball Learning Outcomes at The High School Level - Pramdhan, Kartono (STKIP Paasundan Press, 2023)
Passing down is a technique of playing the ball by using the forearm side of the arm either by using one or with two arms simultaneously. A rubber ball is a ball made of elastic rubber in a round shape like a balloon, without being covered with synthetic leather like the original ball. This study aims to find out volleyball learning using rubber balls can improve passing. The research method used is the experimental method with research design using experimental methods with the pretest-posttest type. The population in this study were all class XI SMAN 1 Ciparay totaling 360 people, The sampling technique used was Cluster Random Sampling and the sample was 38 students of class XI-8 SMAN 1 Ciparay. 25, Based on the results of the research on the calculation and analysis of data from the results of the underpass test, it can be concluded that: Modification of learning media using rubber balls has a significant effect on increasing the underpass in volleyball for SMAN 1 Ciparay students.